The Antecedents of Online Purchase Intention During Covid-19: A Serial Mediation Approach - S. Dheepalakshmi; R. Geetha (Qubahan Academic Journal)
The objective of this study is to investigate how consumers’ online shopping experience influence online purchase intention through a serial mediation model using stimulus organism response (SOR) framework. 378 valid responses were collected from online shoppers in India and the data were analyzed using the SPSS Process macro model 6. The findings showed that online shopping experience (OSE) positively influenced online purchase intention (INT). Further, the result supported that trust and attitude has mediation effect between OSE and INT. Finally, the serial mediation results found that trust and attitude together as sequential mediators significantly influenced the impact of OSE on INT. The results offer practical insights for online retailers and the study also delves into the discussion of theoretical contributions.